The “Managed” or Damaged Heart? Emotional Labor, Gender, and Posttraumatic Stressors Predict Workplace Event-Related Acute Changes in Cortisol, Oxytocin, and Heart Rate Variability - Birze, Arija; LeBlanc, Vicki; Regehr, Cheryl; Paradis, Elise; Einstein, Gillian (Frontiers in Psychology, 2020)
Vital to the everyday operation of police services, police communicators (911 call-takers and dispatchers) are persistently subject to imminent challenges in the workplace; they must always be prepared to engage and deal with a wide variety of circumstances that provoke various intense emotions and physiological stress responses. Acute changes in cortisol, oxytocin, and heart rate variability are central to adaptive responses in stressful complex social interactions, but they might also be indicative of physiological dysregulation due to long-term psychosocial stress exposures. Thus, we examine acute stress-induced release of peripheral oxytocin and cortisol along with changes in heart rate variability, and how each relates to persistent workplace stressors and symptoms of posttraumatic stress. Findings indicate chronic forms of gendered workplace stress such as emotional labor, gender role stress and, posttraumatic stress each have differential associations with, and predict physiological responses to, acutely stressful events in the workplace. These associations suggest potential mechanisms through which communicators become more vulnerable to developing stress-related disorders such as posttraumatic stress injuries, especially after cumulative traumatic exposures in this context. The results also suggest potential pathways for the biological embedding of stressful gendered workplace experiences.